CORPORATE ACTION ON PLASTIC POLLUTION (THE BODY SHOP CASE STUDY) - Einjella Patsy; Muhammad Lukman Baihaqi Alfakihuddin; Natasha Angelica Butar Butar; Priscilla Nethania (SEAN Institute, 2023)
In recent years, plastic waste has resulted in numerous negative environmental impacts. To mitigate these effects, businesses have been adopting sustainable practices, including the production of eco-friendly products. The Body Shop, a well-known cruelty-free beauty brand, has implemented its corporate social responsibility initiative,